VINOTHERAPY AND ITS IMPACT ON HEALTH ATTITUDES: THE INNOVATION PERSPECTIVE - Malgorzata Rutkowska-Podolowska; Nina Szczygiel; Grzegorz Podolowski (Institute of Economic Research (IER), 2015)
Evidence from research has not only excluded negative consequence related to moderate consumption of wine, but associated consumption of skin, juice and seeds of grapes in any stage with a protective impact on health. Compounds of wine demonstrate anti-cancer, antioxidant and a defensive for the cardiovascular system results. The 'French paradox' proves that the French suffer from 40% less heart attacks than the Americans consuming 30% more fat what is due to diet including regular modest amounts of wine. The central aspect of this logic is to turn a growing interest in wine consumption for health benefits into innovative solutions with different approaches and make for this purpose also use of areas that have undergone significant transformations over last decades as a results of global dynamical change which offer new consumption patterns seen now as driving forces for stagnating economies of the XXI century. In an attempt to face this interesting tendency, we conducted a study aiming at determining wine consumption patterns in light of overall alcohol consumption and the dimension of health attitudes with perception and awareness of positive effects of moderate amounts of wine consumption on human health. Results demonstrate a still limited consumption of wine in Poland, also for health-related purposes, although a high consciousness of its benefits and application in medicine indicating an increasing awareness in this matter.
Keywords: I12; O13; O30; O35; 330; vinoteraphy; wine consumption; health attitudes; cardiovascular system; innovation